(untitled) (Medical Forum Monthly, 2024)
Objective: The association between serum calcium levels and radiological characteristics of osteoporotic fractures was systematically evaluated, with a focus on their implications for reproductive health and pediatric surgical outcomes in Mirpur, AJK. Study Design: Prospective cohort study. Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology, Radiology and surgery Hospital & Mohi–ud-Din Islamic Medical College, Mirpur AJK from 10 June, 2023 to 10 February, 2024. Methods: Patients diagnosed with osteoporotic fractures were comprehensively assessed for serum calcium levels and radiological findings. Fracture severity and bone mineral density were primarily analyzed, while secondary outcomes, including the relationship between calcium deficiency, reproductive health concerns, and pediatric surgical recovery, were also extensively examined. Results: Significantly lower serum calcium levels were notably observed in patients with osteoporotic fractures compared to non-fracture controls (8.3 ± 0.9 mg/dL vs. 9.3 ± 1.1 mg/dL, p = 0.002). Radiological evaluations clearly indicated pronounced cortical bone thinning and increased trabecular porosity, particularly in postmenopausal women and elderly males. Additionally, faster fracture healing was consistently noted in pediatric patients who received calcium and vitamin D supplementation, whereas prolonged recovery was frequently observed in those with persistently low calcium levels. Conclusion: The critical role of serum calcium levels in osteoporotic fracture management was effectively highlighted by this study. The findings suggest that calcium monitoring should be proactively prioritized to significantly enhance fracture healing, notably improve reproductive health outcomes, and optimally support pediatric surgical recovery in the Mirpur AJK region